¿Are major humanitarian crises ravaging the planet today? Mental mealth (HAITI) - Ruiz, María Teresa; Crespo, Joe (Omnia, 2024)
According to the World Health Organization (WHO), mental disorders account for 14of the global burden of diseases and injuries in adolescents between 10 and 19 years of age (see foot quote 1 below). Globalization has made it possible to have a better understanding of humanitarian crises as well as to be able to act faster in front of a humanitarian emergency. However, the path is not yet clear enough so as to perform an intense, rapid and effective action absolutely necessary in front of any emergency or disaster. The search of policies and actions aimed to strengthen communities to face this type of contexts –that is, to train them to cope with the mental health of their members- is a must. Mental Health is a complex speciality since it deals with the human soul and mind. These recommendations may be fully appreciated when one sees the situation experienced in Haiti by a population that has been and is still hit by several natural catastrophes (several hurricanes and a cholera epidemic), by a persistent inability of the local administration to mobilize resources, and to coordinate and control international resources for the reconstruction of the country